OPTIMASI PEMBAGIAN TUGAS KARYAWAN MENGGUNAKAN METODE HUNGARIAN - Oktovianus R. Sikas; Defita Lusia Olo; Elinora Naikteas Bano (Saintek Lahan Kering, 2022)
Assignment problem is one part of linear programming that can be found in real life. The Assignment problem includes m workers who have n tasks assuming n=m. The division of work is seriously handled by the company so that each employee gets an equal amount of work hours that are determined. This study aims to optimize employee assignments based on minimum operational costs and minimum job completion times using the Hungarian method. Optimization is a mathematical approach that deals with maximum and minimum problems. From the results of the study, after using the Hungarian method, the work completion time on the Kefamenanu Supermarket Metro was 9: 34: 20 (in hours, minutes, seconds). The total operational costs of work incurred by the company if calculated using the Hungarian method with MATLAB software, the results are Rp. 11,141. Furthermore, the order of minimization of employee assignments is obtained as follows: II, VII, I, IV, VI, V and III.